Investigation on the occurrence of ground ULF and its correlation to space ULF prior to the earthquake events / Mohamad Harjs Salleh - Salleh, Mohamad HarIs
These paper focuses on the occurrence of Ground ULF signal prior due to the fact that ULF frequency band is considered as most promising frequency range in ground base observation where electromagnetic earthquake precursors may be found hence the study of I I I magnetic wave is very significant In order to reveal possible earthquake precursor through the changes of ULF Signal, 6 sets of real time data from California region is used as a study case. The observation was made on the day of the earthquake event occur. The data was taken from Qnakefinder websites which owned magnetometer station along the California fault region. The results obtained, demonstrated the theory that magnetometer may detect anomaly in ULF signal several days or a few hours before main shock.